ORGANIZATION OF ACTIVITIES AT THE VILNIUS BASILIAN PRINTING HOUSE (1628–1845) - Kažuro, Ina (Knygotyra, 2017)
The printing house of the Vilnius Basilian monastery stands out as one of the oldest and largest printing houses of the Eastern Rite Catholic Church and the Grand Duchy of Lithuania, the activities of which lasted about 200 years. In this printing house, books were printed in the Polish, Latin, ecclesiastical Slavonic, Lithuanian and Latvian languages. Furthermore, among the books printed by the Basilians were the pieces printed in Italian, French, Greek and English. Following the abolition of the Eastern Rite Catholic Church in 1839, printing operations were not resumed. Instead, all printing equipment was sold out to the printers Teofilius Gluksberg and Abrahami Dworzec as well as to the townsman Gronim Pupkin. The article is the first attempt ever to analyse the organizational aspects of activities in the said printing house such as its localization and premises, legal situation, managers and employees, technical equipment and sales of the printed material. Research of material conditions makes it easier to establish the factors that have contributed to the development and decline of printing activities as well as identify the causes of multilingual multi-denominational printing output in this institutional enterprise. Such research is aimed to better understand the Lithuanian printing business up to the 19th century and provide background information for more comprehensive research in the fields of reading culture, the history of the Basilian order, social history and material culture of Vilnius. Throughout all the periods of its activity, the print shop was located in the territory of the Vilnius Basilian Monastery in the old part of the city close to the Sharp Gates (Lith. Aštrieji vartai), currently the Gates of Dawn (Lith. Aušros vartai). The localization of the Basilian Monastery in the old centre of religious culture and crafts was favourable to developing the activities of the printing house. The founders and sponsors of the 17th century printing house were the metropolitan archbishops of the Eastern Rite Catholic Church, whereas in the second half of the 18th century the sponsorship was taken over by the superiors of the Lithuanian Basilian Province. Until the year 1768, the legal situation of the printing house was based on the right to print books, inherited by the Vilnius Basilian monastery in 1633 from the Vilnius Holy Trinity Fraternity belonging to the Eastern Rite Catholic Church. In 1768, King and Grand Duke Stanislaw Augustus granted the Lithuanian Basilians a special privilege for the printing house, allowing to transfer the Vilnius printing house to Vitebsk, but this privilege was never taken advantage of. The research made it possible to identify a considerable part of the staff working at the printing house. Thus, in the 17th century, the printing shop employed 3 staff members (1 townsman and 2 Basilians), in the 18th century, 5 printers-Basilians were working in the printing house, and in the first half of the 19th century, 5 printers were employed (all of them were hired secular persons). During the period from the second half of the 18th century to the start of the 19th century, in total six prefects were appointed to manage the printing house activities. During the research, the name of one more manager of the printing house – Markel Solokaj – was established. He was appointed as prefect on July 1, 1838, when printing activities were no longer resumed. Hypothetically it could be stated that during the most profitable period of activity, that is, during the period of 1760–1800, printing activities were carried out by about 20 persons. As a rule, the prefects appointed to run the printing house were chosen from the educated monks having the priest’s ordinances. Among the prefects, priest Nicefor Nenicz (1777–1793) was the most successful in running the printing house. In 1760–1800, 4 book-printing machines and 1 one-piece machine for carving press as well as other quality equipment purchased in foreign countries was installed at the printing house. In addition, a letter foundry, a bookbindery and a bookstore were operating in close proximity to the printing house. The printing house conducted a wide range of printing activities such as printing of books, brochures, sheet music and images of religious content, was specialising in accidental printing, etc. In general, the book production process was fairly well organized, and this allowed the printing press to operate continuously and profitably for several decades. However, the prefects of the printing house did not put any effort into developing book distribution channels. Under the circumstances, mediating monasteries, bookshops and publishers started the business of trading books. The print shop itself was not able to organize effective sales. The weak and shaky book trade is evidenced by the announcements of various individuals and companies about the sales of the book Lexykon geograficzny by I. Karpiński (1766), the publication of which appeared among the Lithuanian and Polish periodicals from 1768 to 1829. Only some issues of the publication were subscriptionbased. It could be concluded that it was not only the political pressure of the Russian administration, but also the weak management of book distribution that led the printing press in early 19th century to stagnation.